Carbon dioxide (CO2) dry reforming of glycerol for syngas production over rhenium promoted on Ni-based catalyst supported on santa barbara amorphous 15 ( SBA15) - Jessy Lynn, Jaspin (2017)
The depletion of natural resources is a critical issue as we are running out of raw resources to generate energy thus it is important for us to find alternative ways to replace these non-renewable sources. One of the ways is through the utilization of glycerol as a major feedstock for hydrogen production through dry reforming process. This work focused on the synthesis, characterization and studies on the performance of glycerol dry reforming over Ni-based catalyst supported on SBA-15 and promoted by rhenium (Re). The catalyst Ni/SBA-15 and 3%Re_Ni/SBA-15 were synthesized via wet impregnation technique. The reaction was conducted in stainless steel fixed bed reactor at various temperature (700˚C, 800˚C and 900˚C) and carbon dioxide to glycerol ratios (0.5, 1 and 3). The physicochemical characterizations of the catalysts were analyzed using X-Ray Diffraction (XRD), Brunaeur-Emmett-Teller (BET) multipoint analysis, Scanning Electron Microscopy (SEM), Thermogravimetric analysis (TGA)- Calcination studies, Temperature Programmed Oxidation (TPO- ) and Field Emission Scanning Electron Microscope (FESEM). Based on characterization studies, it was found that 3%Re_Ni/SBA-15 catalyst showed a good performance compared to non-promoted Ni/SBA-15 catalyst. As the result of XRD analysis show smaller crystallite size and indicate fine Ni dispersion on promoted catalyst. For BET analysis, promoted catalyst gave higher specific surface area, bigger pore volume as well as bigger average pore volume. Besides, SEM analysis show promoted catalyst has smooth and creates longitudinal surface which due to small cryrstallite size as depicted in XRD analysis. TGA analysis show that promoted catalyst need more higher temperature to eliminate water vapor in between 30 to 100 ℃. Moreover, 3%Re_Ni/SBA-15 catalyst has been chosen for further study on glycerol conversion and hydrogen yield. The reaction were carried out at fixed temperature 700℃ and carbon to glycerol ratio (1:1). It was found that 3%Re_Ni/SBA-15 catalyst gave higher glycerol conversion and hydrogen yield of 57% and 55% respectively meanwhile Ni/SBA-15 gave lower glycerol conversion and hydrogen yield of 20% and 18% respectively.